Microbiota shaping and bioburden monitoring of indoor antimicrobial surfaces - Mäki, Anita; Salonen, Noora; Kivisaari, Meija; Ahonen, Merja; Latva, Martti (Frontiers in Built Environment, 2023)
Indoor residents are constantly exposed to dynamic microbiota that have significant health effects. In addition to hand hygiene, cleaning, and disinfection, antimicrobial coatings (AMCs) can prevent the spread of infectious diseases in public areas. The sustainable use of antimicrobial-coated products requires an assessment of their pros and cons for human health and the environment. The toxicity and resistance risks of AMCs have been considered, but large-scale genetic studies on the microbial community compositions and resistomes of AMCs are scarce. The use of an AMC can reduce the total number of microbes on a surface but poses the risk of dysbiosis, microbial imbalance, such as the polarized growth of metallophilic, metal- and antimicrobial-resistant, and other survivor bacteria, and the overall reduction of microbial diversity. Loss of diversity may lead to the enrichment of harmful bacteria and an increased risk of communicable or immunological noncommunicable inflammatory diseases (NCDs). In public buildings, such as kindergartens and nursing homes for the elderly, the use of AMCs is likely to increase due to epidemics and pandemics in recent years. Therefore, comprehensive metagenomic research is needed to monitor the effects of AMCs on indoor microbial community compositions and functions. Although the determination of good indoor microbiota and homeostasis is difficult, microbial communities that have health-protective or harmful effects can and should be identified using a metagenomic sequencing approach before the large-scale implementation of AMCs.